2017
DOI: 10.1016/j.seizure.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of anterior thalamic deep brain stimulation in epilepsy: A 11-year, single center experience

Abstract: ATN DBS can be an effective therapy in a variety of patients with DRE. Importantly, we provide evidence that significant therapeutic efficacy can be sustained for up to 11 years. Neurological complications were rather rare, but long-term hardware-related complications should be followed arrectis auribus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 29 publications
4
76
0
3
Order By: Relevance
“…Currently, U.S. Food and Drug Administration (FDA)‐approved chronically implanted intracranial neuromodulation systems include DBS and responsive neurostimulation (RNS). DBS has been used for decades to treat movement disorders and, more recently, to treat neuropsychiatric disorders and epilepsy . DBS systems are modular, consisting of a multicontact lead, an internal pulse generator (IPG), and an extension cable.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, U.S. Food and Drug Administration (FDA)‐approved chronically implanted intracranial neuromodulation systems include DBS and responsive neurostimulation (RNS). DBS has been used for decades to treat movement disorders and, more recently, to treat neuropsychiatric disorders and epilepsy . DBS systems are modular, consisting of a multicontact lead, an internal pulse generator (IPG), and an extension cable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to a randomized study, assessing the effectiveness of hippocampal stimulation in patients with temporal lobe DRE, positive effect in the form of complete disappearance of seizures was found in 50% of patients [60]. According to other studies, it was shown that after 11 years of deep brain stimulation, the attacks were not registered for at least 12 months in only 13.8% of the patients [61].…”
Section: Deep Brain Stimulationmentioning
confidence: 94%
“…59 In a separate study of 29 patients followed for 11 years, DBS of the ANT resulted in a median 70% reduction in total seizures. 96 Similarly to RNS, the DBS trial reported implant site infections in 10% of patients; however, the authors also reported incorrect lead position in 8.2% of the cases (possibly due to variability between frame and frameless implantation procedures). 97 In addition, a 7-year mood and memory outcome study in the DBS trial revealed that 14.8% and 13% of the active stimulation group reported an adverse event related to depression and memory, respectively.…”
Section: Deep Brain Stimulationmentioning
confidence: 97%
“…It is important to note that after 5 years, 16% of patients had demonstrated seizure freedom in the previous 6 months (Table ) . In a separate study of 29 patients followed for 11 years, DBS of the ANT resulted in a median 70% reduction in total seizures …”
Section: Neurostimulation To Treat Epilepsymentioning
confidence: 99%